Tissue engineering with mesenchymal stem cells. - Kuo, C.K (IEEE Engineering in medicine and biology magazine)
The possibilities of using stem cells in place of tissue-specific cells. This article focuses on tissue engineering therapies and presents the potential use of autologous stem cells in place of allogeneic or xenogeneic tissue-specific cells, with an emphasis on adult mesenchymal stem cells. Scaffolds, synthetic extracellular matrices to support cell growth and tissue development, are covered with respect to specific material requirements, scaffold types, and fabrication techniques.